Design and Realization of a Smart Irrigation System on Sloping Lands and Hills - Nguyen, Huy Phuong; Bui, Dang Thanh (Old Journal, 2017)
This paper presents an approach for design and realization of smart irrigation systems on sloping lands and hills. In the proposed system, the data from temperature sensors, humidity sensors, and rain-detection sensors are first acquired, then calculated by using STM32 microcontroller, and transferred to a data center via wireless communication. In addition, a computer-based interface is developed to acquire and monitor the data about trees on the hills. Four smart irrigation modes have been developed for the system in order to perform irrigation for different cases including manual, timing, schedule, and fully automatic modes. The preliminary results show the desired performances of the proposed system when operating with different irrigation modes.